2021
DOI: 10.1021/acs.jmedchem.0c01796
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of GLPG2451, a Novel Once Daily Potentiator for the Treatment of Cystic Fibrosis

Abstract: Cystic fibrosis (CF) is a life-threatening recessive genetic disease caused by mutations in the gene encoding for the cystic fibrosis transmembrane conductance regulator (CFTR). With the discovery of Ivacaftor and Lumacaftor, it has been shown that administration of one or more small molecules can partially restore the CFTR function. Correctors are small molecules that enhance the amount of CFTR on the cell surface, while potentiators improve the gating function of the CFTR channel. Herein, we describe the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…It works upon binding at the interface of the two CFTR’s MSDs [ 49 ]; however, ivacaftor-based treatment results in minor benefit to patients [ 48 ] with only 10% enhanced lung function [ 50 ]. Other potentiators have been identified and are now under preclinical characterization or in drug development pipeline [ 51 53 ], but some of them give off-targets effects [ 54 ]. Despite the current ivacaftor/lumacaftor combination therapy (Orkambi and more recently Trikafta from Vertex Pharmaceuticals) designed for CF patients with the genetic F508del mutation in homozygosity have a good efficacy [ 20 ], treatment of lung pathology in CF would take advantage from antimicrobial compounds with a repairing action of the lung epithelium in addition to a potentiation of CFTR activity.…”
Section: Discussionmentioning
confidence: 99%
“…It works upon binding at the interface of the two CFTR’s MSDs [ 49 ]; however, ivacaftor-based treatment results in minor benefit to patients [ 48 ] with only 10% enhanced lung function [ 50 ]. Other potentiators have been identified and are now under preclinical characterization or in drug development pipeline [ 51 53 ], but some of them give off-targets effects [ 54 ]. Despite the current ivacaftor/lumacaftor combination therapy (Orkambi and more recently Trikafta from Vertex Pharmaceuticals) designed for CF patients with the genetic F508del mutation in homozygosity have a good efficacy [ 20 ], treatment of lung pathology in CF would take advantage from antimicrobial compounds with a repairing action of the lung epithelium in addition to a potentiation of CFTR activity.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules were demonstrated to rescue mutant CFTR carrying G551D, G178R, R334W, S549N or F508del – the latter in combination with either VX-809 or ABBV-2222 – in both cell lines and CF HBE. 73 , 92 , 93 Patch-clamp functional studies showed that ABBV-974 and GLPG-2451 reduce the closed time and increase the open time of CFTR channels by a similar mechanism to that of VX-770, as no additive effects were observed when these molecules were tested together. 73 , 92 , 93 ABBV-3067 is another potentiator developed by Abbvie that was demonstrated to rescue F508del-CFTR in combination with the corrector ABBV-2222, 74 and this combination is currently under clinical investigation (NCT03969888).…”
Section: Cftr Modulator Drugs and Personalized Medicinementioning
confidence: 99%
“… 73 , 92 , 93 Patch-clamp functional studies showed that ABBV-974 and GLPG-2451 reduce the closed time and increase the open time of CFTR channels by a similar mechanism to that of VX-770, as no additive effects were observed when these molecules were tested together. 73 , 92 , 93 ABBV-3067 is another potentiator developed by Abbvie that was demonstrated to rescue F508del-CFTR in combination with the corrector ABBV-2222, 74 and this combination is currently under clinical investigation (NCT03969888). Abbvie also has two other investigational potentiators that are being pre-clinically tested: AC2-2 and AP2.…”
Section: Cftr Modulator Drugs and Personalized Medicinementioning
confidence: 99%
“…6 Most recently, the addition of a second site CFTR corrector agent to a potentiator−corrector combination was shown to give improvement in lung function in both hetero-and homozygous F508del CF patients, leading to the 2019 US registration of the ivacaftor−tezacaftor−elexacaftor (Trikafta) fixed dose combination. 7 Further CFTR potentiator−corrector combinations are in development from AbbVie, with the clinical stage potentiators GLPG1837 2 8 and GLPG2451 3 9 (Figure 1) disclosed, and the broader field of CFTR potentiator discovery has also been recently reviewed. 10 Chronic obstructive pulmonary disease (COPD) is anticipated to shortly become the third leading cause of death globally.…”
Section: ■ Introductionmentioning
confidence: 99%